(untitled) (Acta Entomologica Serbica, 2023)
In this study, the habitat preferences and abundance of Dolichopodidae species in the Inner West Anatolia (Afyonkarahisar, Kütahya and Uşak) were investigated by means of a hand net during the years 2009 to 2011. A total number of 4,327 specimens were gathered belonging to 77 species. The majority of identified species in the study area prefer moist and shaded habitats such as fenlands, reedbeds, moist coniferous woodland and moist grasslands, depending on habitat preference. Almost 45 % of the total number of collected specimens belonged to one species (Syntormon pallipes). Other abundant species were Hydrophorus balticus and Poecilobothrus regalis.